2010
DOI: 10.1158/0008-5472.can-10-1388
|View full text |Cite
|
Sign up to set email alerts
|

FTY720 (Fingolimod) Sensitizes Prostate Cancer Cells to Radiotherapy by Inhibition of Sphingosine Kinase-1

Abstract: Radiotherapy is widely used as a radical treatment for prostate cancer, but curative treatments are elusive for poorly differentiated tumors where survival is just 15% at 15 years. Dose escalation improves local response rates but is limited by tolerance in normal tissues. A sphingosine analogue, FTY720 (fingolimod), a drug currently in phase III studies for treatment of multiple sclerosis, has been found to be a potent apoptosis inducer in prostate cancer cells. Using in vitro and in vivo approaches, we analy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
162
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(166 citation statements)
references
References 41 publications
3
162
0
1
Order By: Relevance
“…Fingolimod (FTY720), an orally active sphingosine inhibitory analogue that we have utilized, was developed to target this pathway, and has recently been approved for use in multiple sclerosis patients to reduce the rate of relapses, presumably by preventing lymphocyte egress from lymphoid organs (36,37). The potential clinical utility of FTY720 is not limited to multiple sclerosis; Pchetski and colleagues previously demonstrated that FTY720 radiosensitizes PC3 and DU145 prostate cancer cells (38). Although our results seem to be at odds with their report, because we only observed radiosensitization of PC3-miR-95 overexpressing cells and not PC3-control cells, this discrepancy may be because of the lower concentration of FTY720 used in our study (0.5 mmol/L) compared with their study (1 mmol/L).…”
Section: Discussionmentioning
confidence: 99%
“…Fingolimod (FTY720), an orally active sphingosine inhibitory analogue that we have utilized, was developed to target this pathway, and has recently been approved for use in multiple sclerosis patients to reduce the rate of relapses, presumably by preventing lymphocyte egress from lymphoid organs (36,37). The potential clinical utility of FTY720 is not limited to multiple sclerosis; Pchetski and colleagues previously demonstrated that FTY720 radiosensitizes PC3 and DU145 prostate cancer cells (38). Although our results seem to be at odds with their report, because we only observed radiosensitization of PC3-miR-95 overexpressing cells and not PC3-control cells, this discrepancy may be because of the lower concentration of FTY720 used in our study (0.5 mmol/L) compared with their study (1 mmol/L).…”
Section: Discussionmentioning
confidence: 99%
“…Concordant studies have shown that SphK1, responsible for S1P synthesis, is instrumental to cancer promotion, progression, and resistance to treatment in vitro and in vivo, notably in prostate cancer (9,19,21,22,31). In complement to preclinical literature, we recently reported the relationship between increased SphK1 activity and relevant clinical features in human prostate cancer resection specimens confirming a central role for the SphK1/ S1P signaling in prostate cancer (7).…”
Section: Discussionmentioning
confidence: 99%
“…The protocols for measurement of ceramide, sphingosine, and S1P have been described in detail previously (9,26).…”
Section: Sphk1 and Serine Palmitoyltransferase Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This drug is currently available for the treatment of multiple sclerosis (28) and has showed anticancer properties in different models of human cancers (8,29,30). This agent moderately inhibits survival of all cell lines, with an IC 50 !…”
Section: Sphk1 Inhibition Partially Restores Sensitivity To Cetuximabmentioning
confidence: 99%